Improving management and effectiveness of home blood pressure monitoring: a qualitative UK primary care study. - Grant, S; Greenfield, S; Nouwen, A; McManus, R (Royal College of General Practitioners, 2015)
Self-monitoring blood pressure (SMBP) is becoming an increasingly prevalent practice in UK primary care, yet there remains little conceptual understanding of why patients with hypertension engage in self-monitoring.To identify psychological factors or processes prompting the decision to self-monitor blood pressure.A qualitative study of patients previously participating in a survey study about SMBP from four general practices in the West Midlands.Taped and transcribed in-depth interviews with 16 patients (6 currently monitoring, 2 used to self-monitor, and 8 had never self-monitored). Thematic analysis was undertaken.Three main themes emerged: 'self' and 'living with hypertension' described the emotional element of living with an asymptomatic condition; 'self-monitoring behaviour and medication' described overall views about self-monitoring, current practice, reasons for monitoring, and the impact on medication adherence; and 'the GP-patient transaction' described the power relations affecting decisions to self-monitor. Self-monitoring was performed by some as a protective tool against the fears of a silent but serious condition, whereas others self-monitor simply out of curiosity. People who self-monitored tended not to discuss this with their nurse or GP, partly due to perceiving minimal or no interest from their clinician about home monitoring, and partly due to fear of being prescribed additional medication.The decision to self-monitor appeared often to be an individual choice with no schedule or systems to integrate it with other medical care. Better recognition by clinicians that patients are self-monitoring, perhaps utilising the results in shared decision-making, might help integrate it into daily practice.